Tantangan Modernitas Hukum Pidana Islam - La Jamaa (Universitas Islam Negeri Jakarta, 2016)
Modernity Challenges of Islamic Criminal Law. One of the challenges facing the Islamic criminal law in the era of modernity is the advancement of science and technology in the fields of medicine and human rights. Science and technology can be used as a analysis method in Islamic criminal law, although the concept of human rights in the era of modernity bore dilemma. In this paper, the author examines some contemporary issues associated with Islamic criminal law that is taking khamr, organ transplant technology, DNA tests and modernity that make a misperception in human rights concept.DOI: 10.15408/ajis.v16i2.4456